Tunable Fiber‐Cavity Enhanced Photon Emission from Defect Centers in hBN. Issue 17 (17th June 2021) - Häußler, Stefan; Bayer, Gregor; Waltrich, Richard; Mendelson, Noah; Li, Chi; Hunger, David; Aharonovich, Igor; Kubanek, Alexander
Abstract: Realization of quantum photonic devices requires coupling single quantum emitters to the mode of optical resonators. In this work, a hybrid system consisting of defect centers in few‐layer hexagonal boron nitride (hBN) grown by chemical vapor deposition and a fiber‐based Fabry–Pérot cavity is presented. The sub 10‐nm thickness of hBN and its smooth surface enable efficient integration into the cavity mode. This hybrid platform is operated over a broad spectral range larger than 30 nm and its tuneability is used to explore different coupling regimes. Consequently, very large cavity‐assisted signal enhancement up to 50‐fold and strongly narrowed linewidths are achieved, which is owing to cavity funneling, a record for hBN‐cavity systems. Additionally, an excitation and readout scheme is implemented for resonant excitation that allows to establish cavity‐assisted photoluminescence excitation (PLE) spectroscopy. This work marks an important milestone for the deployment of 2D materials coupled to fiber‐based cavities in practical quantum technologies. Abstract : A hybrid system consisting of defect centers in few‐layer hexagonal boron nitride (hBN) and a fiber‐based Fabry–Pérot cavity is presented, achieving an up to 50‐fold signal enhancement and strongly narrowed linewidths. Additionally, cavity‐assisted photoluminescence excitation (PLE) spectroscopy is performed. This marks a milestone for the deployment of 2D‐materials coupled to fiber‐based cavities in practical quantum technologies.